NEWEST GEODYNAMICS RECONSTRUCTION OF THE MIDDLE DNIEPER REGION AND ITS MANIFESTATIONS IN THE RELIEF - Shevchuk, V.; Tustanovska, L.; Kravchenko, D.; Hadiatska, К. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Based on a comprehensive structural-morphometric analysis, Earth remote sensing data and GIS analysis, the evolution of the paleorelief of the right bank of the Middle Dnieper in the recent period is reconstructed. Based on the stepwise morphostructural-neotectonic analysis, morphodynamic and evolutionary trends in the landscape relief of this region are traced. Three morphostructures (Kyiv, Obukhiv, Kanevskaya-Trakhtemirovsky blocks) were identified and characterized. Quantitative indicators of the relief were determined during each stage, and the total oscillation amplitudes were analyzed both over short time intervals and for the entire Neogene-Quaternary period. On the whole, the amplitude of fluctuations in the elevations of the relief of the Middle Dnieper in the Neogene-Quaternary period in the northern part was 100 m, in the southern – 135 m. The differentiated nature of neotectonic movements and the change in their activity over time were reconstructed. It was confirmed that the northern regions of the region had an active upward dynamics of movements in the Neogene era, and the southern ones in the Quaternary.The modern stage marks the opposite phenomenon – the north-eastern regions rise again and the south-western ones fall.The obtained data can serve as a basis for analyzing the influence of tectonic movements on the activation of dangerous geological processes within the Middle Dnieper and forecasting their development in the future.
Keywords: structural-morphometric analysis; leveling surface; base surface; neotectogenesis; morphogenesis; tectonic movements; geodynamics